Selection of elephant grass genotypes for resistance to spittlebug - Auad, Alexander Machado; Simões, Amanda Daniela; Pereira, Antonio Vander; Braga, André Luiz Furtado; Sobrinho, Fausto Souza; Lédo, Francisco José da Silva; Moraes, Silvana Viera Paula; Oliveira, Simone Alves; Ferreira, Roberta Botelho (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate genotypes of elephant grass (Pennisetum purpureum Schum.) regarding resistance to the spittlebug Mahanarva spectabilis. For antibiosis evaluation, each plant was infested with six eggs near hatching, thirty days after planting, in a completely randomized design with 30 genotypes and ten repetitions. Forty-five days after the nymphs hatched, the insect survival rate was evaluated on the different genotypes. For nonpreference mechanism evaluation, the size and number of the nymphs per pot were assessed every 15 days, in plants kept at greenhouse, where adults of M. spectabilis were periodically released, in a completely randomized design, with three repetitions per genotype in two sampling periods. Cameroon de Piracicaba, Pioneiro, Cuba 169, Santa Rita, Mineiro Ipeaco, Mercker Comum de Pinda and CNPGL 96-27-3 genotypes were selected for resistance, by antibiosis mechanism. In the study of the nonpreference mechanism, the number and average size of the nymphs varied significantly as a function of the elephant grass genotype. Roxo de Botucatu and Pioneiro genotypes are, respectively, susceptible and resistant check candidates by the antibiosis mechanism, and Cameroon and Cameroon Piracicaba genotypes are promising by the nonpreference mechanism.